ОСОБЕННОСТИ ХУДОЖЕСТВЕННОГО СОДЕРЖАНИЯ В ЛИТЕРАТУРНОЙ РАЗРАБОТКЕ „ВЕЧНЫХ” ОБРАЗОВ (ДОН ЖУАН) - ЛОСКУТНИКОВА, МАРИЯ (Studia Rossica Posnaniensia, 2006)
Comparative analysis of typical principles and methods for literature image in the creative works of Tirso de Molina, G.G. Byron, etc. is investigated in this paper. The image of Don Juan is one of the most symbolic in world literature. There are about two hundred works devoted to the description of this person. He searches for the beauty infinitely. A. Pushkin had taken a Spanish tale as an initial material to create his tragedy Stone Guest. M. Tsvetaeva in her lyrical circle Don-Juan had based on Pushkin’s image concept. However, her approach polemizes with Pushkin’s view of art. Tsvetaeva advanced the woman’s voice of Donna Anna.